National Legislative and Regulatory Activities (OECD Publishing, 2010)
BELARUS Amendments to laws on the use of atomic energy (2009) Criminal law on acts concerning the use of radioactive sources and administrative law for non-criminal violations of radiation safety requirements (2009) EGYPT Law on activities in the nuclear and radiation field (2010) FRANCE Decree establishing a Committee on industrial co-ordination of radioactive waste (2010)Law on the recognition and indemnification of victims of nuclear tests conducted by France (2010) GERMANY Tenth Amendment to the Atomic Energy Act (2010) Act on Environmental Impact Assessment (2009) Radiation Protection Commission (2009) Act on the Protection against Non-ionizing Radiation (2009) International transport of dangerous goods by road (2009) IRELAND Order to amend Regulations on Active Implantable Medical Devices (2010)Amendment to Medical Devices Regulations (2010) ITALY Decree setting out rules for the siting, construction and operation of nuclear installations (2010) ROMANIA Law on the reorganisation of public authorities (2009) Government Decision on the reorganisation of electric power producers (2010) SLOVAK REPUBLIC Amendment of the Atomic Act (2009) SPAIN Law regulating limited investment companies quoted on the real estate market (2009) UKRAINE Overview of recent amendments to laws in the field of nuclear energy (2009)